Assessing the Relationship between Disordered Gamblers with Psychosis and Increased Gambling Severity: The Mediating Role of Impulsivity. (June 2018) - Kim, Hyoun S.; Cassetta, Briana D.; Hodgins, David C.; Tomfohr-Madsen, Lianne M.; McGrath, Daniel S.; Tavares, Hermano
Objective: Recent research suggests that disordered gambling and psychosis co-occur at higher rates than expected in the general population. Gamblers with psychosis also report greater psychological distress and increased gambling severity. However, the mechanism by which psychosis leads to greater gambling symptomology remains unknown. The objective of the present research was to test whether impulsivity mediated the relationship between comorbid psychosis and gambling severity. Method: The sample consisted of 394 disordered gamblers voluntarily seeking treatment at a large university hospital in São Paulo, Brazil. A semistructured clinical interview (Mini-International Neuropsychiatric Interview) was used to diagnosis the presence of psychosis by registered psychiatrists. Severity of gambling symptoms was assessed using the Gambling Symptom Assessment Scale, and the Barratt Impulsiveness Scale–11 provided a measure of impulsivity. Results: Of the sample, 7.2% met diagnostic criteria for psychosis. Individuals with a dual diagnosis of psychosis did not report greater gambling severity. Conversely, dual diagnoses of psychosis were associated with greater levels of impulsivity. Higher levels of impulsivity were also associated with greater gambling severity. Importantly, support for our hypothesised mediation model was found such that impulsivity mediated the association between disordered gambling and psychosis and gambling severity. Conclusion: Impulsivity appears to be a transdiagnostic process that may be targeted in treatment among disordered gamblers with a dual diagnosis of psychosis to reduce problematic gambling behaviours.